EDUCATIONAL AND HISTORICAL TOPICS IN THE VISIONS OF WRITERS OF WESTERN UKRAINE - Bagriy, Maria (Mountain School of Ukrainian Carpaty, 2021)
It is no coincidence that educational and historical themes are relevant in Western Ukrainian literature: in this way, writers-educators sought to show the indomitability of Ukrainians, the invincibility of the national "I", as well as to lift the spirit of the nation that lost the liberation struggle of 1918-1920. to realize the eternal dream of "union with Greater Ukraine". Cults of Kruty heroes, heroes of the Bazaar, Sich Riflemen, heroes of the battles for Makivka, Ukrainian Cossacks, Ivan Mazepa, T. Shevchenko, Lesya Ukrainka, as well as cults of native education and native book, education, Ukrainian, physically healthy, naturally appear in literature. spiritual rich, spokesman for the anti-alcohol movement, gradual farmer and housewife, who not only care about rational management, but profess the principle of "their own", which will lead in the future to economic and political independence of the Ukrainian state, the cult of a new generation of educated farmers, who, using the latest management methods, based on the acquired knowledge, general culture will be able to "gradually" (effectively) manage, become not only wealthy people but also active public figures who will lead others, the cult of a new constellation of cooperators who and farmers, will take care not only of their own material well-being, business, but also to build the nation economic mechanism, the cult of the mother-woman-patriot, nationally-conscious, active Ukrainian woman who cares about the proper national upbringing of children, etc. On these topics, Western Ukrainian literature differed from European literatures of "state peoples" and, of course, from Ukrainian Soviet literature.